A sodium ion battery positive electrode material and its preparation method and application
By using high temperature melting sodium melting sodium melting and carbon plastic fluid on the surface of the metal oxides on the layer -shaped transition metal oxides to form a uniform carbon coverage layer, it solves the problem of mutual change and side reactions in the process of the material in the charging and discharge cycle, which improves the conductivity and conductivity and conductivity and conductivity and conductivity and conductivity. Circular stability has significantly improved the multiplier and cycle performance of the battery.
Patent Information
- Application Number
- CN202311671642.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-12-07
AI Technical Summary
The layered transition metal oxide positive electrode material is prone to phase change and side reactions with the electrolyte during the charge and discharge cycle, and it is difficult to achieve uniform carbon material coating, affecting the material's conductivity and cycle stability.
By using high-temperature molten sodium chloride to form a uniform coating layer on the surface of the layered transition metal oxide material, and using carbon glue to screen and dry outside the sodium chloride coating layer, a uniform carbon precursor layer is formed. This is followed by carbonization to form a uniform carbon coating.
This method effectively improves the conductivity and air stability of the positive pole material, improves the battery's multiplier and circulating performance, and the first Kuron efficiency and the cycle stability of the first Kuron are significantly improved.
Smart Images

Figure CN117577811B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in smart phones, new energy vehicles, energy storage systems and other fields due to their light weight, high energy and power density, and long cycle life. With the large-scale application of electric vehicles and advanced energy storage systems, the demand for lithium continues to increase, leading to a sharp rise in the price of lithium. Sodium-ion batteries have attracted widespread attention due to the abundance of sodium resources, low cost, and similar physical and chemical properties to lithium-ion batteries.
[0003] Layered transition metal oxides have large theoretical capacity and compaction density, especially for use in sodium-ion full batteries, and are therefore considered to be the most promising positive electrode materials for sodium-ion batteries. However, layered oxide positive electrode materials usually undergo multiple phase changes during the charge-discharge cycle, are prone to side reactions with the electrolyte, and have high surface alkalinity, which limits the commercial application of the material. Currently, metal oxides ZrO2, Al2O3, B2O3, metal fluorides AlF3 and NaPO4 are coated on the surface of layered oxide positive electrode materials to prevent transition metal dissolution, reduce adverse side reactions at the interface between the electrolyte and the positive electrode, and improve the air stability and cycle stability of the positive electrode material. However, the above-mentioned coating treatment is prone to uneven coating, and will reduce the conductivity, gram capacity, and rate performance of the material. In addition, this type of layered transition metal oxide is difficult to directly use carbon materials for surface coating. The two are prone to redox reactions at high temperatures, resulting in poor coating effects and a decrease in the performance of the material after coating.
[0004] Based on this, the present invention provides a method for uniformly coating a carbon layer on the surface of a layered transition metal oxide material. The positive electrode material prepared by this method has high conductivity and good air stability, which can effectively improve the rate and cycle performance of the battery. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a sodium ion battery positive electrode material and a preparation method and application thereof. The present invention first uses sodium chloride, which is chemically stable and fusible at high temperature, to coat a layered transition metal oxide material. A uniform coating layer formed on the surface of the layered transition metal oxide material by molten sodium chloride can effectively isolate the contact between the outer coating material and the layered transition metal oxide. Then, a carbon colloid and a sieving treatment are used to form a uniformly coated carbon precursor layer on the outermost layer of the positive electrode material. After carbonization treatment, a uniformly coated carbon layer is formed on the surface of the positive electrode material, thereby effectively improving the conductivity and air stability of the positive electrode material.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:
[0008] (1) mixing a sodium ion battery layered transition metal oxide material and sodium chloride uniformly, and then heating the mixture under an inert atmosphere to obtain a sodium chloride-coated positive electrode material;
[0009] (2) dispersing the sodium chloride-coated positive electrode material prepared in step (1) in a carbon colloid solution, sieving and drying the solution to obtain a positive electrode material coated with a carbon precursor, and then carbonizing the solution under an inert atmosphere. The composite material obtained by the carbonization treatment is washed with an organic solvent to obtain the positive electrode material for a sodium ion battery.
[0010] Furthermore, the layered transition metal oxide material of the sodium ion battery is Na x [Ni a Fe b Mn c M' d ]O2, wherein M' is selected from one or more of Cu, Zn, Mo, Co, Cr, Al, Ti, 0.6≤x≤1.2, a+b+c+d=1.
[0011] Furthermore, the sodium ion battery layered transition metal oxide material Na x [Ni a Fe b Mn c M' d ]O2, 0≤a≤0.5, 0≤b≤0.4, 0≤c≤0.5, 0≤d≤0.4.
[0012] Furthermore, in step (1), the mass ratio of the sodium ion battery layered transition metal oxide material to sodium chloride is preferably 80-98:2-20.
[0013] Furthermore, in step (1), the temperature of the heating treatment is preferably 750-1000° C., and the time of the heating treatment is preferably 0.5-5 h.
[0014] Furthermore, in step (2), the carbon colloid solution comprises a carbon material, a binder and a saturated sodium chloride solution; wherein the carbon material can be selected from one or more of carbon nanotubes, graphene, graphite powder and conductive carbon black; the binder can be selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride, gum arabic, polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, sodium alginate and sodium polyacrylate; and the solvent of the saturated sodium chloride solution is selected from one or more of N-methylpyrrolidone, ethanol, isopropanol and acetone.
[0015] More preferably, the mass proportion of the binder in the carbon glue is 2%-8%; the mass proportion of the carbon material in the carbon glue is 2%-10%.
[0016] Furthermore, in step (2), the sieving process has a sieving mesh size of 300-1000 mesh; and the drying process is a spray drying process.
[0017] Furthermore, in step (2), the temperature of the carbonization treatment is 700-900° C., and the time of the carbonization treatment is 0.5-5 h.
[0018] Furthermore, in step (2), the organic solvent is a good solvent for sodium chloride, selected from one or more of ethanol, glycerol and ether solvents.
[0019] The second aspect of the present invention provides a sodium ion battery positive electrode material prepared by the preparation method described in the first aspect.
[0020] Furthermore, the sodium ion battery positive electrode material comprises a layered transition metal oxide, a sodium chloride coating layer and a carbon coating layer distributed in sequence from the inside to the outside.
[0021] A third aspect of the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the second aspect.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. Based on the prior art, it is difficult for carbon materials to be directly and evenly coated on the surface of layered oxide materials, and it is easy to undergo redox reactions with layered oxide materials under high temperature conditions, thereby affecting the electrochemical properties of positive electrode materials; the present invention provides a method for preparing a positive electrode material for a sodium ion battery, which can uniformly coat a carbon layer on the surface of a layered transition metal oxide material, and the prepared positive electrode material for a sodium ion battery has high conductivity and good air stability, and a sodium ion battery made of the positive electrode material exhibits excellent rate performance and cycle stability. The details are as follows: The present invention first uses sodium chloride, which is chemically stable and fusible at high temperatures, to coat the layered transition metal oxide material. The sodium chloride melts under high temperature conditions, thereby forming a uniform coating layer on the surface of the layered transition metal oxide material, which can effectively isolate the outer coating material from contact with the layered transition metal oxide; based on this, the carbon colloid is mixed with the positive electrode material modified by sodium chloride, and after screening and drying, a uniformly coated carbon precursor layer is formed on the outermost layer of the positive electrode material. The uniform coating layer formed based on sodium chloride effectively isolates the carbon material from the positive electrode material, thereby avoiding the redox reaction between the two at high temperatures. After carbonization treatment, a uniformly coated carbon layer is formed on the surface of the positive electrode material; the positive electrode material prepared by the above preparation method not only maintains a high gram capacity, but also its conductivity and air stability are significantly improved.
[0024] 2. The present invention not only allows the carbon material to be uniformly coated on the outer surface of the positive electrode material to form a uniform carbon coating layer by introducing a sodium chloride transition layer, but also effectively improves the problem that the gram capacity of the positive electrode material is significantly reduced due to coating, so that the prepared positive electrode material can effectively improve the rate performance and cycle stability of the battery while maintaining a high gram capacity. Compared with sodium ion batteries made of unmodified layered transition metal oxides, sodium ion batteries made of the positive electrode materials prepared by the present invention show higher first coulombic efficiency and better cycle stability under high rate conditions, for example, the capacity retention rate of 200 cycles at a current density of 1C can reach more than 95%. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the formation of the positive electrode material of the sodium ion battery of the present invention.
[0026] Figure 2 This is a graph showing the first charge and discharge curve of a sodium ion battery prepared using the sodium ion battery positive electrode material prepared in Example 1 as the positive electrode active material.
[0027] Figure 3 This is a graph showing the first charge and discharge curves of a sodium ion battery prepared using the sodium ion battery positive electrode material prepared in Comparative Example 1 as the positive electrode active material.
[0028] Explanation of the accompanying drawings: 1-sodium chloride coated positive electrode material, 2-carbon precursor coated positive electrode material, 3-sodium ion battery positive electrode material, a-sodium ion battery layered transition metal oxide material, b-sodium chloride layer, c-carbon coating layer. DETAILED DESCRIPTION
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0030] As described in the background technology, the layered transition metal oxide positive electrode materials of sodium ion batteries usually undergo multiple phase changes during the charge and discharge cycle, are prone to side reactions with the electrolyte, and have high surface alkalinity, which limits the commercial application of the materials. At present, in order to improve the air stability and cycle stability of such positive electrode materials, metal oxides, metal fluorides, etc. are usually used to coat the surface of the positive electrode materials, but after the coating treatment of such materials, the positive electrode materials have problems such as low gram capacity and poor conductivity, and due to the uneven coating phenomenon, the effect of improving the air stability of the material is limited; in order to improve the conductivity of the positive electrode material, if the layered transition metal oxide is directly coated with a carbon material, since the two are prone to redox reactions at high temperatures, the coating effect is poor and the performance of the positive electrode material after the coating treatment is reduced.
[0031] In order to solve the above technical problems, the present invention provides a method for preparing a positive electrode material for a sodium ion battery, such as Figure 1 As shown, the following steps are included:
[0032] (1) mixing a sodium ion battery layered transition metal oxide material and sodium chloride uniformly, and then heating the mixture under an inert atmosphere to obtain a sodium chloride-coated positive electrode material 1;
[0033] The sodium chloride coated positive electrode material 1 comprises a sodium ion battery layered transition metal oxide material a and a sodium chloride layer b coated outside the sodium ion battery layered transition metal oxide material a;
[0034] (2) dispersing the sodium chloride-coated positive electrode material prepared in step (1) in a carbon colloid solution, and obtaining a carbon precursor-coated positive electrode material 2 after sieving and drying;
[0035] The carbon precursor-coated positive electrode material 2 comprises a sodium ion battery layered transition metal oxide material a, and a sodium chloride layer b and a carbon coating layer c sequentially coated thereon;
[0036] Then, a carbonization treatment is performed under an inert atmosphere, and the composite material obtained by the carbonization treatment is washed with an organic solvent to obtain the sodium ion battery positive electrode material 3;
[0037] The obtained sodium ion battery positive electrode material 3 includes a sodium ion battery layered transition metal oxide material a and a carbon coating layer c coated thereon.
[0038] Since carbon materials are prone to undergo redox reactions with sodium ion battery layered transition metal oxides at high temperatures, thus affecting the coating effect and the electrochemical properties of the coated layered transition metal oxides, it is difficult to directly use carbon materials to coat sodium ion battery layered transition metal oxides to improve the material's air stability and electrical conductivity. Based on this, the present invention introduces a sodium chloride transition layer and utilizes the insulating effect of the transition layer to prepare a uniformly coated carbon coating layer outside the transition layer, thereby not only avoiding the influence of the formation of the carbon coating layer on the material's gram capacity, but also effectively improving the electrical conductivity and air stability of the positive electrode material after the coating treatment. The details are as follows:
[0039] The present invention firstly utilizes sodium chloride, which is chemically stable and meltable at high temperature, to coat the layered transition metal oxide material. The sodium chloride melts under high temperature conditions, thereby forming a uniform transition coating layer on the surface of the layered transition metal oxide material, which can effectively isolate the contact between the outer coating material and the layered transition metal oxide. Based on this, the carbon colloid is mixed with the positive electrode material modified by sodium chloride, and after screening and drying, a uniformly coated carbon precursor layer is formed on the outermost layer of the positive electrode material. The uniform coating layer formed based on sodium chloride effectively isolates the carbon material from the positive electrode material, thereby preventing the two from undergoing redox reaction at high temperature. After carbonization treatment, a uniformly coated carbon layer is formed on the surface of the positive electrode material. The positive electrode material prepared by the above preparation method not only maintains a high gram capacity, but also its electrical conductivity and air stability are significantly improved.
[0040] In some preferred embodiments, the layered transition metal oxide material for sodium ion batteries is Na x [Ni a Fe b Mn c M' d ]O2, wherein M' is selected from one or more of Cu, Zn, Mo, Co, Cr, Al, and Ti, 0.6≤x≤1.2, 0≤a≤0.5, 0≤b≤0.4, 0≤c≤0.5, 0≤d≤0.4, and a+b+c+d=1. For example, the sodium ion layered transition metal oxide is an O3 phase layered transition metal oxide Na 0.94 [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2.
[0041] In some preferred embodiments, the mass ratio of the layered transition metal oxide material of the sodium ion battery to sodium chloride is 80-98:2-20, such as 80:20, 82:18, 85:15, 88:12, 90:10, 92:8, 95:5, etc., including but not limited to the mass ratios listed above. The mass ratio of the layered transition metal oxide material of the sodium ion battery to sodium chloride is controlled in a suitable range, such as 80-98:2-90, so that the sodium chloride can be evenly coated on the surface of the layered transition metal oxide material of the sodium ion battery after melting, thereby effectively isolating the contact between the carbon material and the layered transition metal oxide, while avoiding excessive sodium chloride content, which affects the gram capacity and cycle stability of the positive electrode material.
[0042] In some preferred embodiments, the sodium ion battery layered transition metal oxide material and sodium chloride are ball-milled and mixed so that the two can be fully mixed to obtain a uniformly dispersed mixed powder.
[0043] In some preferred embodiments, in step (1), the temperature of the heating treatment is 750-1000°C, such as 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, etc., and the time of the heating treatment is 0.5-5h, such as 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, etc. In order to improve the uniformity of sodium chloride coating on the layered transition metal oxide material, the present invention mixes the two uniformly and then performs a heating treatment, so that the surface sodium chloride is melted and uniformly and tightly coated on the surface of the layered transition metal oxide material, but at the same time, the sodium chloride is prevented from decomposing in the process, so the temperature and time of the heating treatment need to be controlled in a suitable range, such as heating at 750-1000°C for 0.5-5h.
[0044] In some preferred embodiments, in step (2), the carbon colloid comprises a carbon material, a binder and a saturated sodium chloride solution; wherein the carbon material may be selected from one or more of carbon nanotubes, graphene, graphite powder, and conductive carbon black, the binder may be selected from one or more of polyvinylidene fluoride, polyvinylidene fluoride, gum arabic, polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, sodium alginate, and sodium polyacrylate, and the solvent of the saturated sodium chloride solution is selected from one or more of N-methyl pyrrolidone, ethanol, isopropanol, and acetone. The present invention uses a carbon colloid comprising a carbon material, a binder, and an organic solvent as a carbon precursor to coat the positive electrode material after the sodium chloride coating treatment, and uses the carbon material and the binder to form a carbon coating layer with better conductivity after carbonization treatment. In addition, the addition of the organic solvent, on the one hand, allows the carbon material and the binder to be mixed more evenly, and at the same time, the binder and the carbon material can be better attached to the sodium chloride coating layer through the organic solvent, and a tightly coated carbon layer is formed after carbonization treatment.
[0045] More preferably, the mass proportion of the binder in the carbon glue is controlled between 2% and 8%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc., and the mass proportion of the carbon material in the carbon glue is controlled between 2% and 10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., including but not limited to the mass proportions listed above.
[0046] In some preferred embodiments, in step (2), the mesh number of the sieving treatment is 300-1000 mesh, and the drying treatment is preferably performed by spray drying. By controlling the mesh number of the sieving treatment and performing a drying treatment on the positive electrode material coated with the carbon colloid after sieving by spray drying, the surface of the positive electrode material can be uniformly coated with the carbon colloid, and the organic solvent in the carbon colloid is removed after the spray drying treatment to form dry particles, thereby preventing the positive electrode material from aggregating again and affecting the uniformity of the distribution of the surface coating material.
[0047] In some preferred embodiments, in step (2), the temperature of the carbonization treatment is 700-900°C, such as 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, etc., including but not limited to the temperatures listed above, and the time of the carbonization treatment is 0.5-5h, such as 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, etc., including but not limited to the times listed above. The binder and the carbon material in the carbon colloid form a carbon coating layer with a multi-level network structure after carbonization treatment, thereby effectively improving the conductivity of the positive electrode material. At the same time, the sodium chloride coating layer reacts with the carbon at high temperature to generate sodium and carbon tetrachloride, which is beneficial to the improvement of the gram capacity of the positive electrode material.
[0048] In some preferred embodiments, in step (2), the organic solvent can be selected from one or more of anhydrous glycerol, anhydrous ethylene glycol, and anhydrous ethanol, and the organic solvent is used to remove the residual sodium chloride in the positive electrode material.
[0049] The present invention also provides a sodium ion battery positive electrode material, which is prepared by the above preparation method.
[0050] In addition, the present invention also provides a sodium ion battery, comprising the above-mentioned sodium ion battery positive electrode material.
[0051] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0052] Example 1
[0053] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0054] (1) Layered transition metal oxide materials Na 0.94 [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2(NFM) and sodium chloride were mixed by ball milling at a mass ratio of 9:1, and the obtained mixed powder was kept at 750°C for 2h under N2 atmosphere to obtain NFM&CM;
[0055] (2) mixing polyvinylidene fluoride, carbon nanotubes and saturated sodium chloride NMP solution in a mass ratio of 2.5:2:95.5 to obtain a carbon glue solution;
[0056] The NFM&CM prepared in step (1) is dispersed in a carbon glue solution, sieved (100 mesh), spray-dried to obtain a NFM&CM@C precursor, and then heat-treated at 780°C for 1 hour to obtain a composite material NFM&CM@C;
[0057] The prepared composite material NFM&CM@C is dispersed in anhydrous glycerol and stirred and washed, wherein the mass ratio of the composite material NFM&CM@C to anhydrous glycerol is 1:5, and the sodium ion battery positive electrode material is obtained after drying.
[0058] Example 2
[0059] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0060] (1) Layered transition metal oxide materials Na 0.94 [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2(NFM) and sodium chloride were mixed by ball milling at a mass ratio of 9:1, and the obtained mixed powder was kept at 750°C for 2h under N2 atmosphere to obtain NFM&CM;
[0061] (2) mixing polyvinylidene fluoride, carbon nanotubes and saturated sodium chloride NMP solution in a mass ratio of 2.5:4:93.5 to obtain a carbon glue solution;
[0062] The NFM&CM prepared in step (1) is dispersed in a carbon glue solution, sieved (100 mesh), spray-dried to obtain a NFM&CM@C precursor, and then heat-treated at 780°C for 1 hour to obtain a composite material NFM&CM@C;
[0063] The prepared composite material NFM&CM@C is dispersed in anhydrous glycerol and stirred and washed, wherein the mass ratio of the composite material NFM&CM@C to anhydrous glycerol is 1:5, and the sodium ion battery positive electrode material is obtained after drying.
[0064] Example 3
[0065] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0066] (1) Layered transition metal oxide materials Na 0.94 [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2(NFM) and sodium chloride were mixed by ball milling at a mass ratio of 9:1, and the obtained mixed powder was kept at 750°C for 2h under N2 atmosphere to obtain NFM&CM;
[0067] (2) mixing polyvinylidene fluoride, carbon nanotubes and saturated sodium chloride NMP solution in a mass ratio of 5:2:93 to obtain a carbon glue solution;
[0068] The NFM&CM prepared in step (1) is dispersed in a carbon glue solution, sieved (100 mesh), spray-dried to obtain a NFM&CM@C precursor, and then heat-treated at 780°C for 1 hour to obtain a composite material NFM&CM@C;
[0069] The prepared composite material NFM&CM@C is dispersed in anhydrous glycerol and stirred and washed, wherein the mass ratio of the composite material NFM&CM@C to anhydrous glycerol is 1:5, and the sodium ion battery positive electrode material is obtained after drying.
[0070] Example 4
[0071] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0072] (1) Layered transition metal oxide materials Na 0.94 [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2(NFM) and sodium chloride were ball-milled at a mass ratio of 8:2, and the obtained mixed powder was kept at 750°C for 2h under N2 atmosphere to obtain NFM&CM;
[0073] (2) mixing polyvinylidene fluoride, carbon nanotubes and saturated sodium chloride NMP solution in a mass ratio of 2.5:2:95.5 to obtain a carbon glue solution;
[0074] The NFM&CM prepared in step (1) is dispersed in a carbon glue solution, sieved (100 mesh), spray-dried to obtain a NFM&CM@C precursor, and then heat-treated at 780°C for 1 hour to obtain a composite material NFM&CM@C;
[0075] The prepared composite material NFM&CM@C is dispersed in anhydrous glycerol and stirred and washed, wherein the mass ratio of the composite material NFM&CM@C to anhydrous glycerol is 1:5, and the sodium ion battery positive electrode material is obtained after drying.
[0076] Example 5
[0077] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0078] (1) Layered transition metal oxide materials Na 0.94 [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2(NFM) and sodium chloride were mixed by ball milling at a mass ratio of 9:1, and the obtained mixed powder was kept at 900°C for 2h under N2 atmosphere to obtain NFM&CM;
[0079] (2) mixing polyvinylidene fluoride, carbon nanotubes and saturated sodium chloride NMP solution in a mass ratio of 2.5:2:95.5 to obtain a carbon glue solution;
[0080] The NFM&CM prepared in step (1) is dispersed in a carbon glue solution, sieved (100 mesh), spray-dried to obtain a NFM&CM@C precursor, and then heat-treated at 780°C for 1 hour to obtain a composite material NFM&CM@C;
[0081] The prepared composite material NFM&CM@C is dispersed in anhydrous glycerol and stirred and washed, wherein the mass ratio of the composite material NFM&CM@C to anhydrous glycerol is 1:5, and the sodium ion battery positive electrode material is obtained after drying.
[0082] Example 6
[0083] This embodiment relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operations are as follows:
[0084] (1) Layered transition metal oxide materials Na 0.94 [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2(NFM) and sodium chloride were mixed by ball milling at a mass ratio of 9:1, and the obtained mixed powder was kept at 750°C for 4 h under N2 atmosphere to obtain NFM&CM;
[0085] (2) mixing polyvinylidene fluoride, carbon nanotubes and saturated sodium chloride NMP solution in a mass ratio of 2.5:2:95.5 to obtain a carbon glue solution;
[0086] The NFM&CM prepared in step (1) is dispersed in a carbon glue solution, sieved (100 mesh), spray-dried to obtain a NFM&CM@C precursor, and then heat-treated at 780°C for 1 hour to obtain a composite material NFM&CM@C;
[0087] The prepared composite material NFM&CM@C is dispersed in anhydrous glycerol and stirred and washed, wherein the mass ratio of the composite material NFM&CM@C to anhydrous glycerol is 1:5, and the sodium ion battery positive electrode material is obtained after drying.
[0088] Comparative Example 1
[0089] In this comparative example, the layered transition metal oxide material Na 0.94 [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2(NFM) was ball-milled and set aside.
[0090] Comparative Example 2
[0091] This comparative example relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operation is as follows:
[0092] (1) Layered transition metal oxide materials Na 0.94 [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2(NFM) and sodium chloride were mixed by ball milling at a mass ratio of 9:1, and the obtained mixed powder was kept at 750°C for 2h under N2 atmosphere to obtain NFM&CM;
[0093] (2) dispersing the NFM&CM prepared in step (1) in N-methylpyrrolidone, sieving (100 mesh), spray drying to obtain NFM&CM, and then heat-treating at 850° C. for 3 h to obtain a composite material NFM&CM;
[0094] The prepared composite material NFM&CM is dispersed in anhydrous glycerol and stirred and washed, wherein the mass ratio of the composite material NFM&CM@C to anhydrous glycerol is 1:5, and the sodium ion battery positive electrode material is obtained after drying.
[0095] Comparative Example 3
[0096] This comparative example relates to the preparation of a positive electrode material for a sodium ion battery, and the specific operation is as follows:
[0097] (1) Layered transition metal oxide materials Na 0.94 [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was heated at 750℃ for 2h in N2 atmosphere to obtain NFM;
[0098] (2) mixing polyvinylidene fluoride, carbon nanotubes and saturated sodium chloride NMP solution in a mass ratio of 2.5:2:95.5 to obtain a carbon glue solution;
[0099] The NFM prepared in step (1) is dispersed in a carbon colloid solution, and after sieving (100 meshes) and spray drying, a NFM@C precursor is obtained, and then the precursor is heat-treated at 780° C. for 1 h to obtain a composite material NFM@C;
[0100] The prepared composite material NFM@C is dispersed in anhydrous glycerol and stirred and washed, wherein the mass ratio of the composite material NFM&CM@C to anhydrous glycerol is 1:5, and the sodium ion battery positive electrode material is obtained after drying.
[0101] Application and performance characterization
[0102] 1. Assembly of button battery
[0103] The positive electrode materials prepared in the above examples and comparative examples were respectively used as positive electrode active materials to assemble button-type batteries, as follows:
[0104] The positive electrode active material, conductive carbon, and PVDF were dissolved in N-methylpyrrolidone in a mass ratio of 90:5:5, stirred evenly, and coated on aluminum foil. After vacuum drying at 100°C, the positive electrode sheet was obtained by roller pressing; then the positive electrode sheet, the counter electrode sheet (metallic sodium), the electrolyte (1 mol / L NaPF6 EC:DEC=1:1) and the glass fiber separator were assembled into a battery.
[0105] 2. Performance Testing
[0106] The air stability of the positive electrode materials prepared in the above examples and comparative examples and the first coulombic efficiency, discharge capacity and cycle stability of the assembled button cells were tested as follows:
[0107] First coulombic efficiency test: first place the button battery in a 25±2℃ environment for 8h, then charge it to 4.0V at a constant current of 0.05C, and the obtained capacity is recorded as the 0.05C charging capacity, then let it stand for 5min, then discharge it to a voltage of 3.0V at a constant current of 0.1C, and the obtained capacity is recorded as the 0.1C discharge capacity, and finally stop running. The first coulombic efficiency is 0.1C discharge capacity / 0.05C charging capacity.
[0108] Discharge capacity test corresponding to current density of 0.2C: first place the button battery in a 25±2℃ environment for 8h, then charge it to 4.0V with a constant current of 0.2C, then let it stand for 5min, then discharge it to a voltage of 2.0V with a constant current of 0.2C, then let it stand for 5min, then charge it to 4.0V with a constant current of 0.2C, let it stand for 5min, then discharge it to a voltage of 2.0V with a constant current of 0.2C, the obtained capacity is the discharge capacity corresponding to 0.2C, finally stop running and record the second discharge capacity as the discharge capacity corresponding to 0.2C.
[0109] 1C cycle 200 cycles capacity retention rate: first place the button battery in a 25±2℃ environment for 8h, then charge it to 4.0V at 1C constant current, then let it stand for 5min, then charge it at 4.0V constant voltage to a current of 0.05C, let it stand for 5min, then discharge it to 2.0V at 1C constant current, cycle it 200 times, finally stop running, record the 1st and 200th discharge capacities, and the capacity retention rate is the 200th discharge capacity / 1st discharge capacity.
[0110] The test results are shown in Table 1 below:
[0111] Table 1
[0112]
[0113]
[0114] It can be seen from Table 1 that compared with the uncoated modified layered transition metal oxide (Comparative Example 1), Examples 1 to 6 introduce a sodium chloride transition layer on the surface of the layered transition metal oxide and then perform a carbon coating treatment to prepare a sodium ion battery positive electrode material, which effectively improves the conductivity and stability of the positive electrode material, so that the sodium ion battery prepared therefrom not only maintains a high discharge capacity, but also significantly improves the first coulombic efficiency and the cycle performance at high rate.
[0115] It can be seen from Examples 1 to 3 that the composition of the carbon colloid will affect the gram capacity, conductivity and air stability of the positive electrode material. Compared with Example 1, Example 2 increases the content of carbon nanotubes in the carbon colloid, and the carbon coating formed thereby can improve the conductivity of the positive electrode material, thereby facilitating the performance of the rate performance and improving the cycle stability at high rates, but the excessive amount of carbon nanotubes reduces the gram capacity of the positive electrode material and causes the first coulomb efficiency of the battery to decrease; Compared with Example 1, Example 3 increases the content of the binder in the carbon colloid, thereby increasing the thickness of the carbon coating layer. Based on the increase in the thickness of the carbon coating layer, the first efficiency and cycle stability of the battery are improved compared with Example 1, but the gram capacity of the positive electrode material decreases due to excessive carbon coating material.
[0116] It can be seen from Examples 1, 5, and 6 that, within an appropriate temperature range, by increasing the temperature of the heat treatment or extending the time of the heat treatment, the prepared positive electrode material has better performance. This is because the increase in the temperature of the heat treatment and the extension of the time are conducive to the melting of sodium chloride, thereby forming a more uniform and tight coating layer on the surface of the layered transition metal oxide, which is beneficial to isolating the carbon material from the layered transition metal oxide, thereby avoiding the reaction between the two affecting the coating effect and the performance of the positive electrode material.
[0117] It can be seen from Example 1, Comparative Example 2 and Comparative Example 3 that only preparing a sodium chloride coating layer on the surface of the layered transition metal oxide or directly introducing a carbon material for coating does not effectively improve the performance of the layered transition metal oxide, and the performance characterization data of the sodium ion battery made from the positive electrode material prepared in Comparative Example 3 show that the gram capacity of the positive electrode material prepared by directly using carbon colloid to coat the layered transition metal oxide surface is significantly reduced, and the first efficiency and cycle performance of the sodium ion battery made therefrom are reduced.
[0118] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The following steps are involved: (1) mixing a sodium ion battery layered transition metal oxide material and sodium chloride uniformly, and then heating them under an inert atmosphere to obtain a sodium chloride-coated positive electrode material; the heating treatment temperature is 750-1000° C., and the heating treatment time is 0.5-5 h; the mass ratio of the sodium ion battery layered transition metal oxide material to sodium chloride is 80-98:2-20; (2) The sodium chloride-coated positive electrode material prepared in step (1) is dispersed in a carbon colloid, and after screening and drying, a carbon precursor-coated positive electrode material is obtained, and then carbonization is performed under an inert atmosphere, and the composite material obtained by carbonization is washed with an organic solvent to obtain the sodium ion battery positive electrode material; the carbon colloid comprises a carbon material, a binder and a saturated sodium chloride solution; the solvent of the saturated sodium chloride solution is selected from one or more of N-methylpyrrolidone, ethanol, isopropanol and acetone; the mass proportion of the binder in the carbon colloid is 2%-8%; the mass proportion of the carbon material in the carbon colloid is 2%-10%.
2. The preparation method according to claim 1, characterized in that: In step (1), the sodium ion battery layered transition metal oxide material is Na x [Ni a Fe b Mn c M' d ]O2, wherein M' is selected from one or more of Cu, Zn, Mo, Co, Cr, Al, Ti, 0.6≤x≤1.2, a+b+c+d=1.
3. The preparation method according to claim 1, characterized in that: In step (2), The carbon material is selected from one or more of carbon nanotubes, graphene, graphite powder, and conductive carbon black; The binder is selected from one or more of polyvinylidene fluoride, gum arabic, polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, sodium alginate, and sodium polyacrylate.
4. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the carbonization treatment is 700-900°C, and the time of the carbonization treatment is 0.5-5 h.
5. The preparation method according to claim 1, characterized in that: In step (2), the organic solvent is selected from one or more of ethanol, glycerol and ether solvents.
6. A sodium ion battery positive electrode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 5.
7. A sodium ion battery, characterized in that: Contains the sodium ion battery positive electrode material according to claim 6.
Citation Information
Patent Citations
Sodium-ion battery cathode material and preparation method thereof
CN103227325A
Method for preparing three-dimensional microsphere surrounded by nitrogen-doped carbon nano sheets embedded with Sb@Sb2O3 core-shell structure nano particles
CN110767885A